Reduced occurrence of childhood cancer in twins compared to singletons: protection but by what mechanism? - Murphy, M; Bunch, K; Chen, B; Hemminki, K (Wiley-Liss, 2008)
Background: Several small studies combined have suggested that twins develop fewer childhood cancers than singletons. The national Swedish Family-Cancer Database contains information on a large population of multiple births providing an unbiased dataset for the estimation of cancer risk in twins. Lifelong cancer incidence in these twins has already been reported as similar to that in singleton births. In contrast, the present paper presents robust estimates of a significantly reduced childhood cancer risk in twins to age 15. Methods: Standardised incidence ratios (SIR) were used to measure cancer risk for twins, taking the corresponding rates for singletons as reference. Rates were adjusted for age, sex, period of birth, and residential area. Follow up data cover the period 1958-2002. Results: Overall childhood cancer risk was significantly reduced in all twins (SIR 0.81 [95% CI: 0.69-0.94]) as was the risk for Wilms tumour (SIR 0.34 [95% CI: 0.09-0.88]). These significant reductions in risk were both driven by effects in the same sex twins (overall cancer SIR 0.77 [95% CI: 0.64-0.93], Wilms tumour 0.12 [95% CI: 0.00-0.71]). Leukaemia risk was also significantly reduced for same sex twins (SIR 0.69 [95% CI:0.47-0.97]). Conclusions: Our study provides the evidence that twins experience less childhood cancer than singletons. The risk reduction is most marked for Wilms tumour but may, to a varying extent, be true for a number of childhood neoplasms.